Pattern formation during the impact of a partially frozen binary droplet on a cold surface - Kant, Pallav; Müller-Groeling, Henrik; Lohse, Detlef (Physical review letters, 2020)
The impact of a droplet on an undercooled surface is a complex phenomenon as it simultaneously instigates several physical processes that cover a broad spectrum of transport phenomena and phase transition. Here, we report and explain an unexpected but highly relevant phenomenon of fingered growth of the solid phase. It emerges during the impact of a binary droplet that freezes from the outside prior to the impact on the undercooled surface. We establish that the presence of presolidified material at the advancing contact line fundamentally changes the resulting dynamics, namely, by modifying the local flow mobility that leads to an instability analogous to viscous fingering. Moreover, we delineate the interplay between the interfacial deformations of the impacting droplet and patterned growth of the solid phase as disconnected patterns emerge at faster impacts.
Gesehen am 09.12.2020